PENGARUH KUALITAS PRODUK,PROMOSI DAN LOKASI TERHADAP KEPUTUSAN MENGINAP DI GRAND ORCHARDZ HOTEL KEMAYORAN - Ade Pristiwani; Meylani Tuti (LPPM Universitas Asa Indonesia, 2022)
This study intends to analyze the effect of product quality, promotion, and location on purchasing decisions. Participants in this study were visitors who stayed at Grand Orchardz. The sampling technique used was accidental sampling with a total of 211 respondents. Multiple linear regression analysis is the method used. Research findings indicate that location, promotion, and product quality have a major influence on guests' decisions to stay at Grand Orchardz Hotel Kemayoran either partially or simultaneously